Quality of life among adults with less severe malocclusions seeking orthodontic treatment - Narmina Sandlund; Idil Burt; Robert Schibbye (Acta Odontologica Scandinavica)
Objective: Severe malocclusions affect Oral Health Related Quality of Life (OHRQoL), but the effects of less severe malocclusions are underexplored. This study investigates OHRQoL and psychological well-being in adults with less severe malocclusion, but high subjective need of orthodontic treatment.